THE ROLE OF NGOs IN PROMOTING WOMEN EMPOWERMENT IN CAMEROON (1990-2010) - NJWENG, Kah Asanji (Graduate School of International Studies Ajou University, 2011)
ABSTRACT This research seeks to understand how NGO activities, as well as government policies in Cameroon are empowering women and hence promoting their rule in the development process of Cameroon. For in Cameroon women’s abilities and knowledge are usually not recognized the effort towards sustainable economic development. Customary laws and cultural practices go a long way in placing women in subordinate positions and yet the governments haven’t done anything about it, hence empowering women with their rights and knowledge will mean reducing these vices and NGOs are to be on the drivers’ seat for this to be realized.
학위논문(석사)--아주대학교 국제대학원--NGO학과,2011. 1
Keywords: ROLE OF NGOs; WOMEN EMPOWERMENT IN CAMEROON